Amnesty International : . Amnesty International : bulletin mensuel
Since (1979) subtitled: Bulletin mensuel. English ed.: Amnesty International newsletter (ZK 48320). - Spanish ed.: Amnistía Internacional : boletín informativo (ZK 48322).